Muscle strength, body composition, and performance of an elite shot-putter. - Terzis, Gerasimos; Kyriazis, Thomas; Karampatsos, Giorgos; Georgiadis, Giorgos (Int J Sports Physiol Perform, 2012)
PURPOSE: Although muscle mass and strength are thought to be closely related to throwing performance, there are few scientific data about these parameters in elite shot-putters. The purpose of this case report was to present longitudinal data for muscle strength and body composition in relation to performance of an elite male shot-putter. METHODS: A male national champion with the best rotational shot-put performance of 20.36 m (in 2010) was followed from 2003 to 2011 (current age: 29 y). Data regarding body composition (dual X-ray absorptiometry), as well as 1-repetition-maximum muscle strength (bench press, squat, snatch) and rotational shot-put performance, were collected every February for the last 9 y, 4 wk before the national indoor championship event. RESULTS: The athlete's personal-best performances in squat, bench press, and snatch were 175 kg, 210 kg, and 112.5 kg, respectively. His peak total lean body mass was 92.4 kg, bone mineral density 1.55 g/cm2, and lowest body fat 12.9%. His shot-put performance over these 9 years was significantly correlated with 1-repetition-maximum squat strength (r = .93, P < .01), bench press (r = .87, P < .01), and snatch (r = .92, P < .01). In contrast, shot-put performance was not significantly correlated with any of the body-composition parameters. CONCLUSIONS: The results of this case study suggest that elite rotational shot-put performance may not be directly correlated with lean body mass. Instead, it seems that it is closely related with measures of muscle strength.
Keywords: Absorptiometry, Photon; Adiposity; Adult; Athletic Performance; Biomechanical Phenomena; Body Composition; Bone Density; Humans; Male; Muscle Contraction; Muscle Strength; Muscle, Skeletal; rotation; Task Performance and Analysis; Time Factors; Track and field